Assessment results of development of children 3 – 5 years old by the East Asia-Pacific early child development scales (EAP – ECDS) - Trang Nguyen Thi (SEA-CECCEP, 2021)
To obtain authentic evidence for developing and adjusting policies, strategies, programs, and action plans that meet the requirements of the children's overall development in the new situation, the Ministry of Education and Training (MOET) assessed children aged 3 to 5 years old, in conjunction with interviews with parents and caregivers by the EAP - ECDS. The results show the unequal development of children from different demographic groups in 7 domains, weight, and height, using descriptive statistical methods, then comparing and assessing the difference in scores across groups of children. The findings indicate that it is necessary to consider the government and communities' policies and impacts on educational institutions and children's education to make it more suitable for disadvantaged groups such as children in rural areas, mountainous areas, rural areas, and ethnic minority children. Additionally, the program's material for children's care and education should be more appropriate for children aged 3-5 years, particularly 5-year-old children preparing to enter the first grade.